(untitled) - Lan, Yi-Chen (Hersley, PA, 2005)
Global Information Society: Operating Information Systems in a Dynamic Global Business Environment addresses the importance of information technology management and issues in operating information systems in the global dynamic business environment. It embraces discussions of the global information technology theory, frameworks and IT architecture, discovery of global knowledge management, improvement of the global information systems development methodologies, and applications of the latest technologies such as mobile technology and Web services in global information systems development and operations. Global Information Society: Operating Information Systems in a Dynamic Global Business Environment is a collection of new ideas, latest technology applications and experiences in global information systems development and operations. It contributes significantly to the academic, research and corporate business communities.
Keywords: Information resources,Information technology; Management,Management